Chapter I viaggi in un romanzo e i viaggi di un romanzo nel basso medioevo. Il caso del Joufroi de Poitiers - Manetti, Roberta (Studi e saggi, 2021)
In the fiction of the Joufroi de Poitiers, the author, perhaps a native of eastern France, claims to have found his story near Montpellier. His journey is perhaps not imaginary as we have an indication of a place that carries a certain political value, in an era when the French Crown, after having concluded the anti-Albigensian crusade in the mid-thirteenth century, had taken possession of the Midi. Montpellier was likely a free zone for the production and circulation of works of anti-Capetian satire, such as the Occitan novel which goes under the modern title of Flamenca. In fact, composed in the entourage of James I of Aragon in Montpellier, the Flamenca is one of the probable sources of Joufroi de Poitiers.